2014
DOI: 10.1074/jbc.m114.554246
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-200b Suppresses Arsenic-transformed Cell Migration by Targeting Protein Kinase Cα and Wnt5b-Protein Kinase Cα Positive Feedback Loop and Inhibiting Rac1 Activation

Abstract: Background: MiR-200b is able to inhibit tumor cell migration and metastasis, the underlying mechanism is not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…In the highly migratory arsenic-transformed cells and basal mesenchymal-like triple negative breast cancer cells, we found that PKCα expression levels are significantly higher, and re-expression of miR-200b reduced PKCα levels and inhibited cell migration as well as mammary tumor metastasis [42, 66]. Subsequent luciferase reporter assays revealed that miR-200b directly targets the 3′UTR of PKCα.…”
Section: The Mir-200 Family In Cancer Metastasismentioning
confidence: 99%
“…In the highly migratory arsenic-transformed cells and basal mesenchymal-like triple negative breast cancer cells, we found that PKCα expression levels are significantly higher, and re-expression of miR-200b reduced PKCα levels and inhibited cell migration as well as mammary tumor metastasis [42, 66]. Subsequent luciferase reporter assays revealed that miR-200b directly targets the 3′UTR of PKCα.…”
Section: The Mir-200 Family In Cancer Metastasismentioning
confidence: 99%
“…Taken together, these results indicate that miR-200b down-regulation plays a causal role in arsenite-induced cell malignant transformation and tumorigenesis. In addition, our further follow-up studies also demonstrated that down-regulation of miR-200b plays critical roles in promoting arsenic-transformed cell migration, invasion and tumor angiogenesis (Wang et al, 2012b, 2013, 2014b). Moreover, significant down-regulation of miR-200c level in arsenic-transformed human bronchial epithelial (HBE) cells was recently also observed by other group (Xu et al, 2015a).…”
Section: The Role Of Mirnas In Metal Carcinogen-induced Cell Maligmentioning
confidence: 58%
“…The miRTar algorithm identified 372 miRNAs predicted to target the PRKCA 3 ′ UTR, including three of our temperature-responsive miRNAs. PRKCA targeting by hsa-miR-200b (Wang et al 2014), hsa-miR-216b (Deng et al 2013), hsa-miR-203 (Wang et al 2013), and hsa-miR-24-2 * (Martin et al 2014) have been confirmed experimentally. PKCα levels have been shown to increase with increasing levels of hsa-miR-328 in A549 cells (Arora et al 2011).…”
Section: Figure 5 Functional Analysis Of the Pkcαmentioning
confidence: 60%